Selective ring opening of methylcyclopentane over surface-decorated Ir–Co bimetallic catalysts synthesized by galvanic replacement reaction. Issue 107 (3rd November 2016) - Wang, Zhen; Zheng, Aiguo; Zheng, Renyang; Li, Mingfeng; Li, Huifeng; Xu, Guangtong; Xia, Guofu
Abstract : We present a novel galvanic replacement to synthesize supported Ir–Co bimetallic catalysts, with most Ir atoms preferentially decorated onto the surface of Co instead of the SiO2 support for the selective ring-opening of methylcyclopentane. Abstract : Surface-decorated Ir–Co bimetallic catalysts were synthesized by a modified galvanic replacement reaction and evaluated by the selective ring opening (SRO) of methylcyclopentane (MCP). Inductively coupled plasma atomic emission spectroscopy (ICP-AES) was utilized to characterize the catalyst synthesis process, and H2 -temperature-programmed reduction (H2 -TPR) was performed to characterize the reduction behavior of the calcined catalysts and oxidation resistance of the reduced catalysts. Transmission electron microscopy (TEM) analysis was used to characterize metallic particle size distribution. The reactor evaluation results show quite different behaviors in conversion and product selectivity of the surface-decorated Ir–Co/SiO2 and monometallic Ir/SiO2 . At optimized Ir content, MCP conversion and mass-specific rate of SRO are significantly higher when catalyzed by surface-decorated Ir–Co/SiO2 than by monometallic Ir/SiO2 . Moreover, compared with Ir/SiO2, Ir–Co/SiO2 has decreased 2-methylpentane selectivity but improved n -hexane selectivity. These catalytic behaviors were found to correlate with the surface-decorated bimetallic structure consisting of Co/SiO2 decorated with surface Ir atoms.